Guía didáctica para desarrollar la investigación acción en el aula en la enseñanza de las Ciencias Naturales de los estudiantes de básica media del centro de educación básica “Álvarez Sánchez Colombia” de la parroquia Gualel, cantón y provincia de Loja, período lectivo 2012-2013 - Ojeda Azuero, Paola Elizabeth (2015)
Thisworkisframedinactionresearchintheclassroom teachingofNatural SciencesstudentsofBasicMedia,Centerof BasicEducation "ÁlvarezSánchez Colombia”theGualelparish,countyandprovinceofLoja,periodschool2012-2013.Accordingtothevariablesandindicatorsofthetopic, ageneralobjective was formulated: Designing a tutorial to develop action research in the classroom,teachingNaturalScienceSchooland the aforementioned period. Themethods usedin the development ofthis researchwere:Historical–Logical, analytical,deductive, descriptive,inductive,deductive hypotheticalstatistician whohelpedcollect, quantify andstandardizetheinformation andthus draw conclusions ,recommendations andalternative guidelines. Moreover,thetechniqueusedwasthesurvey;itwasappliedtoteachersand students. With the results obtained by the appointed technical, it proceeded to compare the goals, showing that it is a priority, necessary and essential to develop an educational guide for developing action research in the classroom teaching of Natural Sciences students Basic Media Center Basic Education '' 'Alvarez Sanchez Colombia,' 'which a methodology was developed to verify the great results that it is action research in the classroom teaching of natural sciences, because, constitutes an urgent requirement to develop better and at an early age the research capability of the students. With the results obtained by the appointed technical, proceeded to compare the goals, showing that it is a priority, necessary and essential to develop an educational guide to develop action research in the classroom teaching of natural sciences for students of Basic Media Center Basic Education '' 'Alvarez Sanchez Colombia,' 'which a methodology was developed to verify the great results that have Action research in the classroom teaching of natural sciences, because, constitutes an urgent requirement to develop better and at an early age the research capability of the students